Complete Maya programming an extensive guide to MEL and the C++ API - Gould, David A. D. (San Francisco, CA : Morgan Kaufmann Publishers, 2003)
Learning Maya, the world's leading 3D animation and effects package, is a challenge, especially for those who want to master Maya's versatile programming features in addition to its built-in tools. Finally, here is a practical, step-by-step guide that shows how to use Maya to its fullest potential, beginning with the basics. Readers of Complete Maya Programming will first gain a thorough understanding of Maya's inner workings, and then learn how to customize and extend Maya with scripts and plugins that take control and productivity to new levels. Users new to programming can apply Maya's easy scripting language MEL (Maya Embedded Language), while more advanced users can work with the C++ API (Application Progamming Interface). Both a fundamental tutorial for Maya beginners and a solid reference for experienced developers, Complete Maya Programming is every user's guide to Maya mastery. * Provides a multitude of real-world examples illustrating applications of Maya programming. * Demonstrates how to use MEL to control Maya, customize its interface, automate procedures, and more * Details how to use the C++ API to modify Maya functionality and develop tools and features to meet any need * Explains when to use MEL, when to use the C++ API, and how to use them together * Ideal for technical directors, developers, or anyone wishing to to master Maya * Provides a storehouse of MEL scripts and C++ source code, glossary, and list of resources, available at www.davidgould.com.
1 Introduction; 2 Fundamental Maya Concepts; 3 MEL; 4 C++ API, Appendices: A: Additional Resources; B: MEL for C Programmers; C: Further Reading.
Includes bibliographical references (p. 465-467) and index.
Keywords: Maya (Computer file); Three-dimensional display systems; Computer animation; Computer graphics; C++ (Computer program language); Electronic books